Proceedings of the 29th ACM International Conference on Multimedia 2021
DOI: 10.1145/3474085.3475240
|View full text |Cite
|
Sign up to set email alerts
|

Depth Quality-Inspired Feature Manipulation for Efficient RGB-D Salient Object Detection

Abstract: RGB-D salient object detection (SOD) recently has attracted increasing research interest by benefiting conventional RGB SOD with extra depth information. However, existing RGB-D SOD models often fail to perform well in terms of both efficiency and accuracy, which hinders their potential applications on mobile devices and real-world problems. An underlying challenge is that the model accuracy usually degrades when the model is simplified to have few parameters. To tackle this dilemma and also inspired by the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(21 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…To underline the importance of texture-aware features for COD, Ren et al 11 presented a refinement module based on deep texture perception. Zhang et al 26 suggested a confidence-aware COD framework to prevent deep networks from being overconfident. In the latest research, Pang et al 27 proposed a mixed-scale triplet state network, namely ZoomNet.…”
Section: Methodsmentioning
confidence: 99%
“…To underline the importance of texture-aware features for COD, Ren et al 11 presented a refinement module based on deep texture perception. Zhang et al 26 suggested a confidence-aware COD framework to prevent deep networks from being overconfident. In the latest research, Pang et al 27 proposed a mixed-scale triplet state network, namely ZoomNet.…”
Section: Methodsmentioning
confidence: 99%
“…To testify the validity of our model, we conduct comprehensive experiments on five datasets with 17 SOTA methods, including A2dele [6], BiANet [10], CDINet [7], CMWNet [14], CoNet [8], D3Net [9], DANet [5], DCFNet [13], DFMNet [15], DSNet [4], DSA2F [16], HDFNet [11], ICNet [17], JL-DCF [18], SMEG [19], SSF [20], and UC-Net [21]. Quantitative comparison: Table 1 shows the quantitative results of the M 2 DFNet and other methods on five datasets.…”
Section: Comparisons With Sota Methodsmentioning
confidence: 99%
“…Comparison with the State-of-the-Arts 1) Comparison Methods: We compare our model with 13 state-of-the-art RGB-D based SOD methods, including MMCI [14],TANet [15], DMRA [18], ICNet [48], A2dele [66], S2MA [67], DRLF [38], CCAFNet [68], JL-DCF [41], CPFP [19], D3Net [13], DQSD [21] and DFMNet [69]. Specially, the qualities of depth images are also considered in the last three methods, i.e., CPFP [19], D3Net [13], DQSD [21] and DFMNet [69]. For all the methods mentioned here, we use either the implementations with their default parameter settings or the saliency maps provided by their authors for fair comparisons.…”
Section: B Implementation Detailsmentioning
confidence: 99%